Establishing the Authorship of Two Wooden Icons From the Museikon Collection, Alba Iulia - Olivia Florena Nemeș; Constantin Măruțoiu; Dan Nemeș; Victor Constantin Măruțoiu; Ana Dumitran; Marin Cotețiu; Teofil Tia; Cristian Tigae (Journal of Spectroscopy)
This study sought to obtain information regarding the authorship of two old wooden icons from the “Museikon” collection, a museum dedicated to icons located in the historical city of Alba Iulia. The stylistic and theological analyses indicated a possible author; to support this hypothesis, nondestructive physicochemical investigations were carried out, which were compared with those carried out on an icon with a known author (signed icon) located in the collection of the Metropolitan Museum in Cluj-Napoca. The nondestructive physical–chemical analyses performed, using energy-dispersive x-ray fluorescence and Fourier-transform infrared spectroscopy, provided information about the materials used to create the works of art. The results indicated the use of similar materials and techniques for the creation of works of art: gold leaf, cinnabar, copper green, lead white, iron red, umber, carbon black—used as pigments, and egg yolk—used as the binder in the tempera technique (and probably, linseed oil, constituting a variation known as tempera grassa) are the common materials observed. The omnipresence of white lead applied over the ground and the brown lead color suggests the appearance of plattnerite as a degradation product, which strengthens the connection between the icons. Thus, the physical–chemical investigations support the hypothesis of the common author (Grigore Ranite) suggested by the theological and stylistic analysis.